The Effect of Competence and Work Environment on Employee Performance with Work Discipline as a Mediating Variable - Victoria, Reny Ayu; Herawati, Aty (Jurnal Ilmiah Sumber Daya Manusia, 2026)
This study aims to examine the effect of competence and work environment on employee performance, with work discipline as a mediating variable, at the Directorate General for the Acceleration of Development of Disadvantaged Regions (Ditjen PPDT). Employee competence is regarded as a key factor that can affect their performance within a specific work environment. Meanwhile, a conducive work environment can enhance employee productivity. In this context, work discipline is considered a mediating variable that links the effects of competence and the work environment on employee performance. This study used a quantitative approach, administering a questionnaire via Google Forms to 130 employees. The data analysis techniques used were descriptive analysis and Partial Least Squares (PLS). The study's results show that competence and the work environment positively affect work discipline. Work discipline has been proven to positively affect employee performance. Competence and the work environment are also shown to positively affect employee performance, with work discipline acting as a partial mediator. These findings provide insights for Ditjen PPDT on the importance of managing employee competence, the work environment, employee performance, and work discipline to improve performance and productivity.